2022
DOI: 10.1002/wene.450
|View full text |Cite
|
Sign up to set email alerts
|

A review of 100% renewable energy scenarios on islands

Abstract: Globally, more than 740 million people live on islands which are often seen as ideal environments for the development of renewable energy systems. Hereby, they play the role to demonstrate technical solutions as well as political transition pathways of energy systems to reduce greenhouse gas emissions. The growing number of articles on 100% renewable energy systems on islands is analyzed with a focus on technical solutions for transition pathways. Since the first “100% renewable energy systems on islands”‐arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 243 publications
(587 reference statements)
0
7
0
Order By: Relevance
“…This has improved only marginally with 72% of about 666 known 100% RE system analysis articles at the end of 2021. Many of the known 100% RE system analyses for the Global South cover off-grid analyses of individual villages or smaller regions or smaller islands [436], such as the very well investigated La Réunion [437], Galapagos [438] or Canary Islands [126], so that the relative share of countrylevel analyses are substantially smaller. We apply the definition of the Global South according to Dados and Connell [439].…”
Section: H Overcoming the Lack Of 100% Renewable Energy Systems Analy...mentioning
confidence: 99%
“…This has improved only marginally with 72% of about 666 known 100% RE system analysis articles at the end of 2021. Many of the known 100% RE system analyses for the Global South cover off-grid analyses of individual villages or smaller regions or smaller islands [436], such as the very well investigated La Réunion [437], Galapagos [438] or Canary Islands [126], so that the relative share of countrylevel analyses are substantially smaller. We apply the definition of the Global South according to Dados and Connell [439].…”
Section: H Overcoming the Lack Of 100% Renewable Energy Systems Analy...mentioning
confidence: 99%
“…As of today, a large number of studies, summarised in [8][9][10], indicate that a 100% RE system can be achieved globally at low cost. Hundreds of studies show the benefit of 100% RE systems [10,11], which is confirmed for the UK and Ireland by Meschede et al [12].…”
Section: Introductionmentioning
confidence: 74%
“…state or region; city, village or off-grid; islands). Islands are researched globally with 65 publications identified until mid-2021, with almost 100 articles by mid-2022 [60]; however, most of the island states in the Caribbean and the Pacific are still not researched as shown in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The roughly 100 articles on 100% RE systems on islands are reviewed in more detail [60], along with further review articles with an island focus [61], [62], [63], [64], [65].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation